2020
DOI: 10.1186/s12998-019-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health, health behaviours and demographic profile of patients attending an Australian university student-led osteopathy clinic

Abstract: Background: Profiles of health professions practice can inform pre-professional education, provide evidence to assist with interprofessional practice, and inform policy development. An understanding of the profile of patients seeking osteopathy care is emerging. Current research suggests that musculoskeletal presentations predominate with approximately one-third of patients presenting with co-morbid diseases. There is little data on these presentations in Australian osteopathy practice. This study aimed to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The range of regions for the presenting musculoskeletal complaint is consistent with previous work both in the same clinical environment [22,24] and the Australian osteopathy profession more broadly [17,32].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The range of regions for the presenting musculoskeletal complaint is consistent with previous work both in the same clinical environment [22,24] and the Australian osteopathy profession more broadly [17,32].…”
Section: Discussionsupporting
confidence: 85%
“…Although patients are primarily presenting to the clinic with a musculoskeletal complaint, a proportion of these patients also present with a history of one of the common chronic diseases reported in the Australian population [1,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the Victoria University (Melbourne, Australia) Human Research Ethics Committee (HRE15-035). The study utilised a consecutive sampling design and data analysed in the current work is part of a larger study into the health behaviours, demographics and experiences of patients attending for musculoskeletal care at the clinic [22].…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge the GLSS has not been used to investigate the life satisfaction of patients seeking care for musculoskeletal complaints. We have previously identified that those seeking osteopathy care in the student-led clinic environment report high levels of SWL with a single-item measure [22]. The aim of the current study was to evaluate the relationship of life satisfaction with other health demographics and behaviours, in patients seeking care for musculoskeletal complaints.…”
Section: Introductionmentioning
confidence: 99%